Genetic and epigenetic dynamics affecting anthocyanin biosynthesis in potato cell culture. (September 2020) - D'Amelia, Vincenzo; Villano, Clizia; Batelli, Giorgia; Çobanoğlu, Özmen; Carucci, Francesca; Melito, Sara; Chessa, Mario; Chiaiese, Pasquale; Aversano, Riccardo; Carputo, Domenico
Highlights: StMYBATV is a potato R3-MYB anthocyanin negative regulator. StMYBATV could interfere with the MBW complex formation in successive subculture. MSAP-analysis evidenced a higher methylation level in purple cells than whites. Ribosomial protein genes showed a different methylation in purple vs white cells. Abstract: Anthocyanins are antioxidant pigments widely used in drugs and food preparations. Flesh-coloured tubers of the cultivated potato Solanum tuberosum are important sources of different anthocyanins. Due to the high degree of decoration achieved by acylation, anthocyanins from potato are very stable and suitable for the food processing industry. The use of cell culture allows to extract anthocyanins on-demand, avoiding seasonality and consequences associated with land-based-tuber production. However, a well-known limit of cell culture is the metabolic instability and loss of anthocyanin production during successive subcultures. To get a general picture of mechanisms responsible for this instability, we explored both genetic and epigenetic regulation that may affect anthocyanin production in cell culture. We selected two clonally related populations of anthocyanin-producing (purple) and non-producing (white) potato cells. Through targeted molecular investigations, we identified and functionally characterized an R3-MYB, here named StMYBATV . This transcription factor can interact with bHLHs belonging to the MBW (R2R3-MYB, bHLH and WD40) anthocyanin activator complex and, potentially, may interfere with its formation. Genome methylation analysis revealed that, for several genomic loci, anthocyanin-producing cells were more methylated than clonally related white cells. In particular, we localized some methylation events in ribosomal protein-coding genes. Overall, our study explores novel molecular aspects associated with loss of anthocyanins in cell culture systems.